Participatory landing site development for artisanal fisheries livelihoods: user´s manual - Verstralen, K.M.; Lenselink, N.M.; Ramírez, R.; Wilkie, M.; Johnson, J.P. (Rome (Italy), 2004)
Sumario (En)
Ilus.; 25 ref.
no. 466
Keywords: PESCA ARTESANAL; PRODUCCION PESQUERA; PLANES DE DESARROLLO; PLANIFICACION